Type 2 Diabetes Modifies Skeletal Muscle Gene Expression Response to Gastric Bypass Surgery - Barberio, Matthew D.; Dohm, G. Lynis; Pories, Walter J.; Gadaleta, Natalie A.; Houmard, Joseph A.; Nadler, Evan P.; Hubal, Monica J. (Frontiers in Endocrinology, 2021)
Introduction Roux-en-Y gastric bypass (RYGB) is an effective treatment for type 2 diabetes mellitus (T2DM) that can result in remission of clinical symptoms, yet mechanisms for improved skeletal muscle health are poorly understood. We sought to define the impact of existing T2DM on RYGB-induced muscle transcriptome changes. Methods Vastus lateralis biopsy transcriptomes were generated pre- and 1-year post-RYGB in black adult females with (T2D; n = 5, age = 51 ± 6 years, BMI = 53.0 ± 5.8 kg/m2) and without (CON; n = 7, 43 ± 6 years, 51.0 ± 9.2 kg/m2) T2DM. Insulin, glucose, and HOMA-IR were measured in blood at the same time points. ANCOVA detected differentially expressed genes (p < 0.01, fold change < |1.2|), which were used to identify enriched biological pathways. Results Pre-RYGB, 95 probes were downregulated with T2D including subunits of mitochondrial complex I. Post-RYGB, the T2D group had normalized gene expression when compared to their non-diabetic counterparts with only three probes remaining significantly different. In the T2D, we identified 52 probes upregulated from pre- to post-RYGB, including NDFUB7 and NDFUA1. Conclusion Black females with T2DM show extensive downregulation of genes across aerobic metabolism pathways prior to RYGB, which resolves 1 year post-RYGB and is related to improvements in clinical markers. These data support efficacy of RYGB for improving skeletal muscle health, especially in patients with T2DM.